2016
DOI: 10.26719/2016.22.12.872
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence, knowledge and attitudes among primary healthcare professionals: a study from Jordan

Abstract: This was a questionnaire-based cross-sectional study of 400 healthcare professionals recruited from primary healthcare centres in northern Jordan between April and October 2015. The questionnaire included questions about smoking behaviour, risks, opinions and providing anti-smoking counselling. More than 80% of participants reported that smoking-free policies were not enforced at primary healthcare centres. Compared to hospitals and the general population, smoking was less prevalent among primary healthcare pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
1
6
0
1
Order By: Relevance
“…The results of the current study revealed that the majority of the participants agreed that clinicians need more training in tobacco assessment and cessation interventions (86.4%) and that tobacco cessation should be a standard part of cancer treatment interventions (87.0%). These results are in concordance with other national studies as well as international studies 29,34 . Thus, results of our study, as well as other national and international studies, show that health care providers believe in the importance of SCC practice.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the current study revealed that the majority of the participants agreed that clinicians need more training in tobacco assessment and cessation interventions (86.4%) and that tobacco cessation should be a standard part of cancer treatment interventions (87.0%). These results are in concordance with other national studies as well as international studies 29,34 . Thus, results of our study, as well as other national and international studies, show that health care providers believe in the importance of SCC practice.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, they are higher than the international prevalence in the region. [ 9 30 31 ] Occupational stress has been cited as a reason for rates higher than the general population. [ 32 ] The reasons for the higher smoking prevalence among PHC physicians compared to health care professionals in hospital settings[ 33 34 ] is less clear and an area for further research.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why training was not associated with favorable practice as it has been in other studies. [ 10 38 39 ] Given that the percentage of training among primary care physicians in the region is not satisfactory,[ 10 24 27 30 ] the importance of high quality, sustained, evidence-based training programs are especially important. Guidelines recommend that smoking cessation counseling and brief advice be integrated into all health systems.…”
Section: Discussionmentioning
confidence: 99%
“…related to smoking a major cause of risk factors for chronic obstructive pulmonary disease (COPD) by looking at the symptoms caused by a cough or wet cough and shortness of breath [26], [27] . The effects of smoking are associated with an increased risk of cardiovascular disease [28] . The study also reveals the economic problems of families as a result of smoking.…”
Section: Theme 3: the Effects Caused By Smoking Behaviormentioning
confidence: 99%
“…Smoking habits in health workers do not look at a specific time. Health workers reveal smoking if there is an opportunity [28] .…”
Section: Theme 4: Interpersonal and Situational Influencementioning
confidence: 99%